Kisah Al-Qur'an dalam Tafsir Modern: Peninjauan Narasi Kisah Nabi Sulaiman dan Harut dan Marut dalam Q. 2:102 Menurut Tafsir al-Azhar Karya Hamka - Jesinta Moza Mustika (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2023)
This article provides a detailed analysis of the presentation of Qur'anic stories in contemporary tafsir, with a specific focus on examining the nature and characteristics of modern tafsir. The current approach employed to differentiate classical and modern tafsir has primarily relied on periodization, making it inadequate in addressing the fundamental inquiry regarding the distinguishing characteristics of tafsir's various realities, encompassing both classical and modern iterations. The scholarly discourse surrounding contemporary tafsir subsequently transitions from examining the chronological classification of tafsir to exploring the distinct and varied nature of Qur'anic interpretation as an observable phenomenon. This article aims to provide a focused analysis of Tafsir Al-Azhar, a prominent contemporary exegesis authored by the Indonesian scholar Hamka. The primary objective of this study is to examine Hamka's exegesis of the narrative verses found in the Qur'an. The purpose of selecting this theme is to identify the unique characteristics of modern tafsir, which distinguish it from classical tafsir. This study aims to examine the process of producing modern tafsir, with a particular focus on the interpretation of Qur'anic verses that pertain to the narrative of Prophet Sulaymān, as well as Hārūt and Mārūt mentioned in Q. 2: 102. The contention put forth in this article posits that the categorization of commentaries as classical or modern cannot be definitively determined by the inclusion or exclusion of isrā'īliyāt, as it will invariably be intertwined with the interpretation of Quranic verses pertaining to narratives. However, contemporary scholars of exegesis have revisited a longstanding subject that has historically posed challenges within the Islamic community. This pertains to the question surrounding the validity and significance of isrā'īliyāt literature employed in the interpretation of religious texts. In this particular scenario, there is a tendency among scholars to dismiss isrā'īliyāt narrations that remain subject to debate among both classical and contemporary mufassirs, as well as narratives that lack rational basis.